2018
DOI: 10.1111/jphp.12981
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin sensitized the antitumour effects of irradiation in promoting apoptosis of oesophageal squamous-cell carcinoma through NF-κB signalling pathway

Abstract: We have well-recapitulated the pathological properties and therapeutic response of ESCC with established cell lines derived from clinical samples. We further demonstrated the significantly synergistic effect of curcumin on IR-elicited cell apoptosis in ESCC both in vitro and in vivo. Our data suggested the potential therapeutic values of curcumin for future clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…In vitro experiments with lung cancer cells showed down-regulation of EGFR-and NFkB-AKT-pathway leading to inhibition of proliferation, apoptosis induction and radiosensitization after Curcumin treatment 22,37 . Also in prostate cancer 23 , oesophageal cancer 38 and in head and neck squamous cell carcinoma cells 24 radiosensitization by Curcumin was observed and associated with its impact on NFkB-and EGFR-pathways. In pancreatic cancer cell lines radiation-induced NFkB activity was inhibited by Curcumin consequential leading to a significantly higher apoptosis induction 25 .…”
Section: Discussionmentioning
confidence: 95%
“…In vitro experiments with lung cancer cells showed down-regulation of EGFR-and NFkB-AKT-pathway leading to inhibition of proliferation, apoptosis induction and radiosensitization after Curcumin treatment 22,37 . Also in prostate cancer 23 , oesophageal cancer 38 and in head and neck squamous cell carcinoma cells 24 radiosensitization by Curcumin was observed and associated with its impact on NFkB-and EGFR-pathways. In pancreatic cancer cell lines radiation-induced NFkB activity was inhibited by Curcumin consequential leading to a significantly higher apoptosis induction 25 .…”
Section: Discussionmentioning
confidence: 95%
“…The expression of the proliferation marker Ki-67, angiogenesis markers (CD31 and VEGF), and NF-κB-regulated genes decreased in tumor tissues, leading to the enhanced susceptibility of cancer cells to radiation and suppression of tumor growth. Liu et al (2018a) also demonstrated that curcumin potentiated the anticancer effect of radiation in ESCC cell lines by inhibiting the NF-κB pathway. Treatment with curcumin in an irradiated environment promoted apoptosis induction in cancer cells and prolonged survival in xenograft mice.…”
Section: The Anticancer Mechanism Of Action Of Curcuminmentioning
confidence: 91%
“…In five different human esophageal squamous cell lines ESCC-07, ESCC-12, ESCC-19, ESCC-27, and ESCC-31, curcumin increased radiation-induced apoptotic death primarily through inhibition of the NF-κB signaling pathway. Pretreatment with curcumin also suppressed tumor progression and decreased both the tumor volume and weight of ESCC-07 xenograft mice that were previously exposed to fractionated radiotherapy [ 51 ]. When low doses of curcumin (2.5 μΜ) were combined with radiation in human colon cancer HT-29 cells, a stronger inhibitory effect on cell proliferation was observed, due to modulation of expression of DNA repair-related genes, including Cyclin H (CCNH), DNA Ligase 4 (LIG4) and Polynucleotide Kinase 3′-Phosphatase (PNKP).…”
Section: Curcumin As a Radiosensitizer In Various Malignant Tumors An...mentioning
confidence: 99%